Зависимость термоупругого состояния охлаждаемой монокристаллической лопатки от азимутальной ориентации кристалографических осей - Воробьев, Юрий Сергеевич; Овчарова, Н. Ю.; Берлизова, Т. Ю. (НТУ "ХПИ", 2015)
Рассматривается температурное и термоупругое состояния охлаждаемой монокристаллической лопатки со сложной вихревой системой охлаждения и каналами для выхода охлаждающего воздуха. Задача определения напряженно деформируемого состояния лопатки под действием температурных полей и центробежных сил решается методом конечных элементов. Рассмотрено влияние ориентации кристаллографических осей, на распределение и величину термоупругих напряжений по объему лопатки.

The thermal and thermo-elastic states of the single crystal cooled blade with the complex vortex cooling system and channels for output of the cooling air are considered. Temperature fields of cooled blades are determined by the temperature of gas and cooling air. They cause thermal expansion of the blade, which should be considered in case of definition of the clearances in the labyrinth sealings. Due to the large temperature gradients in such blades large thermoelastic stresses are arises. All this leads to the need to solve the thermal and thermoelastic problem for determining the stress strain state of the blade under the influence of temperature fields and centrifugal forces. Static stress strain state of the blade is determined by taking into account the temperature fields and centrifugal forces. The problem is solved by finite element method. The value of maximum stress depends mostly from the temperature condition of the blade, but the maximum stresses arising in the joint action of the centrifugal forces and temperature fields, but do not achieve the tensile strength. The influence of the orientation of the crystallographic axes on the distribution and value of thermoelastic stresses by volume of blade are considered. The stress distribution by volume the blades have rather complex character. When the vortex system of cooling, the channels for cooling air are arranged at an angle to the longitudinal axis of the blade. If change the orientation of the crystallographic axes occurs redistribution of the stress and changes the whole picture of the stress-strain state of the blades. Since the largest stress intensity can be in a new area of the blade, they will also depend on the geometrical features of this area and its temperature. If change the axial orientation of the crystallographic axes, the greatest stress intensity repeating periodically through the 900. The results of research allow estimating the stress-strain state of the cooled single crystal blades in the inhomogeneous temperature field with the taking into account of the influence of the crystallographic axes, which is of practical interest.
Dependence of thermoelasticity status of the cooling monocrystalline blades from azimuthal orientation crystallographic axes
Keywords: газотурбинные двигатели; температурные поля; центробежные силы; термоупругие напряжения; монокристаллический материал; cooled blade; temperature fields; centrifugal forces; thermoelastic stresses; single crystal material